SISTEM PEMINJAMAN BUKU PADA PERPUSTAKAAN STMIK KRISTEN NEUMANN INDONESIA MENGGUNAKAN QR CODE - Monica F Sebayang; Eliasta Ketaren (UPPM, 2018)
The process of borrowing books at the STMIK Christian Neumann Indonesia library, always experiences problems or problems, namely the process of borrowing books is still done manually and not yet using a system on a computer. For that, we need a system that makes it easy to process book data and the process of borrowing books will be a fast, accurate, and precise system using QR Code as a tool for storing book data and for scanning book data using laptop cameras. So in this case, the authors designed a system with the programming language Visual Basic 2010 and Microsoft Office Access as the database. The results of this study indicate that the use of a book lending system using QR Code helps library staff in the process of borrowing and returning books.